Clinical and strategic outcomes of metastatic synovial sarcoma on limb - Jami, Sayed Abdulla; Mobarak, Siam Al; Jiandang, Shi; Xi, Zhu; Tanvir, M M Sohel; Sutradhar Monilal, Sonjoy (International Journal of Health Sciences, 2020)
Objective: Synovial sarcoma (SS) is one of the most frequent malignant soft-tissue tumors, and nearly 65% arise in the lower extremities. Survival prediction and the risk factors of the patients are poorly understood. Thus, this study examined the survival and prognostic variables of metastatic limb SS (LSS). Methods: Clinical data of LSS patients with metastasis at the presentation from 1975 to 2017 were obtained from the Surveillance, Epidemiology, and End Results database program database. Kaplan–Meier method was used to describe the survival curves. Univariate and multivariate Cox regression analysis were conducted to reveal the real prognostic predictors. Results: Male predominance was observed in the metastatic LSS group from a total number of 217 patients. This population was composed of 49.8% not other specified subtype, 32.7% spindle cell subtype, 17.1% biphasic subtype, and 0.5% epithelioid cell subtype. The 3-year overall survival (OS) and cancer-specific survival (CSS) rates of the entire group were 27.2% and 28.3%, respectively. Tumor size <10 cm, surgery, radiotherapy, and chemotherapy were calculated as independent predictors of improved OS and CSS by multivariate analyses. Conclusion: SS is still a disease with a poor prognosis. This can increase the survival rate and time by the well-planned treatment.